Critical Social Marketing: Assessing the Cumulative Impact of Alcohol Marketing on Youth Drinking - Gordon, Ross (2011)
ABSTRACT Alcohol related harm is one of the major public health and societal concerns in the UK. Per capita alcohol consumption has risen considerably over the last twenty years and binge drinking has increased. Alcohol related harms including crime and social disorder, lost productivity, family breakdown and health harms such as rising incidence of liver disease and increases in alcohol related hospital admissions, are considerable. Particular concern has focused upon alcohol and young people, with levels of youth binge drinking in the UK among the highest in Europe and alcohol related hospital admissions of young people increasing. Furthermore, youth drinking behaviours are strong predictors of alcohol dependence in later life and contribute to long term health harms. As a result there has been an increased focus on factors that may potentially influence youth drinking behaviours including alcohol marketing. The evidence base on the impact of alcohol marketing on youth drinking has developed since the topic was first examined in the early 1980s. Recent systematic reviews have suggested a causal link between alcohol marketing and youth drinking behaviour. However gaps in the evidence base remain. The research project presented in this PhD contains six publications which aim to address these gaps, being the first longitudinal consumer study on the impact of alcohol marketing on youth drinking in the UK. The study used a critical social marketing framework to assess the cumulative impact of alcohol marketing on youth drinking, with findings intended to help upstream social marketing efforts, inform policy and regulation and targeted behaviour change interventions. The project examined the impact of alcohol marketing across a comprehensive range of communications channels including less well researched areas such as new media and sponsorship. The project involved three discrete stages of research. First, a brand website and press audit of contemporary alcohol marketing communications in the UK was conducted, supplemented by interviews with key informants from the marketing profession and regulatory bodies. Second, qualitative focus group research was conducted with young people to explore the role and meaning of alcohol in their lives and their attitudes towards alcohol marketing. Third, a two wave cohort study design featuring a questionnaire survey was conducted to assess the impact of alcohol marketing on youth drinking. The survey consisted of a two part interviewer administered and self completion questionnaire in home with 920 second year school pupils at baseline, and follow up of a cohort of 552 in fourth year. The audit revealed that alcohol marketing is ubiquitous in the UK with most brands having a dedicated website featuring sophisticated content that appeals to youth including music, sport and video games. The press audit found that alcopop brands concentrated advertising in youth magazines, and that supermarket advertising of alcohol was considerable in the printed press. Focus group research revealed a sophisticated level of awareness of and involvement in alcohol marketing among respondents across several channels. Marketing activities often featuring content with youth appeal seemed to influence young people’s well developed brand attitudes. Cross sectional regression analysis found significant associations between awareness of, and involvement with alcohol marketing and drinking status and future drinking intentions. Bivariate and multi-variate longitudinal analysis indicated that alcohol marketing was associated with youth drinking behaviour, including initiation of drinking, and increased frequency of drinking between wave one and wave two. The implications of these findings for theory, practice and public policy are discussed